The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/act11010021
|View full text |Cite
|
Sign up to set email alerts
|

Novel Strategy of Adaptive Predictive Control Based on a MIMO-ARX Model

Abstract: Many industrial processes include MIMO (multiple-input, multiple-output) systems that are difficult to control by standard commercial controllers. This paper describes a MIMO case of a class of SISO-APC (single-input, single-output adaptive predictive controller) based upon an ARX (autoregressive with exogenous variable) model. This class of SISO-APC based on ARX models has been successfully and extensively used in many industrial applications. This approach aims to minimize the barriers between the theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This section presents three multivariable control strategies for water levels in the lower tanks, starting from the linear model in (25). The strategies highlight the interaction and multivariable zero RHP problems.…”
Section: Proposed Control Systems Using Decouplingmentioning
confidence: 99%
See 1 more Smart Citation
“…This section presents three multivariable control strategies for water levels in the lower tanks, starting from the linear model in (25). The strategies highlight the interaction and multivariable zero RHP problems.…”
Section: Proposed Control Systems Using Decouplingmentioning
confidence: 99%
“…In one of the first studies on QTS [19], a decentralized PI control was designed for the QTS configured with a multivariable RHP zero. Other authors have applied internal model control [22], multivariable H ∝ control [3], quantitative feedback control [23], LQG optimal control [24], predictive control [25,26], and distributed model predictive control [27]. More recent works have applied nonlinear techniques to the QTS such as sliding mode control [28,29], feedback linearization [20], fuzzy control [30,31], and neural networks [32], among others.…”
Section: Introductionmentioning
confidence: 99%
“…The ARX structure effectively model various engineering and applied sciences problems such as time series prediction, pneumatic positioning system, wheeled robots, MIMO systems, and behavior modeling [ 78 , 79 , 80 , 81 , 82 ]. The block diagram of the ARX model is presented in Figure 2 , where and are polynomials with a degree and respectively, and given in (1) and (2).…”
Section: Arx Mathematical Modelmentioning
confidence: 99%
“…The autoregressive exogenous model (ARX) is used in different engineering problems such as time series data prediction [ 78 ], pneumatic positioning systems [ 79 ], wheeled robots [ 80 ], multiple-input–multiple-output (MIMO) systems [ 81 ], and human driving behavior modeling [ 82 ]. Various identification techniques were proposed for the parameter estimation of ARX.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that stiction embedding nonlinear MPC only can guarantee good performance in set-points tracking and also stiction compensation. Piñón et al 6 validate the multiple-input multiple-output adaptive predictive controller (MIMO-APC) with the two simulated processes: a quadrotor drone and the quadruple-tank process. The simulation shows excellent set-point tracking behavior in the quadruple tank, in comparison to that with the control strategies previously reported in the literature.…”
Section: Introductionmentioning
confidence: 99%